Вирощування в’єтнамських свиней як один із способів виробництва органічної свинини - Іжболдіна, Олена Олександрівна; Izhboldina, O. O.; Izhboldina, O.; Izhboldina, Е. А.; Izhboldina, Н.; Izhboldina, Е.; Izhboldina, Olena (Дніпровський ДАЕУ, 2019)
У тезах наведено аналітичний матеріал при органічне виробництва свинини на основі в’єтнамської породи свиней. The thesis provides analytical material for the organic pork production on the basis of the Vietnamese breed of pigs.
Growing Vietnamese pigs as one of the ways to produce organic pork
Іжболдіна Олена Олександрівна https://orcid.org/0000-0002-8816-2228
Keywords: органічна свинина; organic pork; молодняк; young pigs; в’єтнамські свині; Vietnamese pigs